89PA phase II trial of adjuvant chemoradiotherapy for patients with high-risk rectal submucosal invasive cancer after local resection. (24th November 2019) - Noguchi, M; Shitara, K; Kawazoe, A; Yamamoto, D; Takii, Y; Saito, Y; Sato, T; Horimatsu, T; Ishikawa, H; Ito, Y; Ito, M; Ikematsu, H
Abstract: Background: Surgery is recommended for patients with high-risk submucosal invasive rectal cancer (SM-RC) after local resection. However, surgery affect patient's quality of life due to stoma placement and impaired anal function. Thus, alternative treatments to prevent local metastasis are anticipated. This study assessed the safety of adjuvant chemoradiotherapy with capecitabine for patients with high-risk SM-RC after local resection. Methods: This single-arm, multicenter, phase II trial enrolled patients with high-risk SM-RC who underwent local resection within 12 weeks prior to enrollment. High-risk SM-RC was defined as the presence of at least one of the following factors: poor differentiation of adenocarcinoma, ≥ 1mm of submucosal invasion, presence of lymphovascular invasion, and grade 2 or 3 of tumor budding. Protocol treatment included 45.0 Gy radiotherapy with conventional fractionation and 825 mg/m 2 capecitabine administered twice daily until the completion of radiotherapy. The primary endpoint was treatment completion rate, with an expected rate of 95% and a threshold of 80%. This study was registered with the University Hospital Medical Information Network, number UMIN000016785. Results: A total of 29 patients from six institutions were enrolled between May 2015 and February 2018. One patient was ineligible. Twenty-three patients completed treatment with a completion rate of 82% (80% confidence interval; range, 69%–91%). The remaining five patients also completed treatment with protocol deviation from the planned treatment schedule. The mean relative dose intensity of capecitabine was 89% (range, 58%–100%). The most common adverse events were radiation dermatitis (54%), anal pain (39%), and anal mucositis (29%). No grade 3 or higher adverse events were reported. Conclusions: Adjuvant chemoradiotherapy using capecitabine demonstrated manageable safety in patients with high-risk SM-RC after local resection. Clinical trial identification: UMIN000016785. Legal entity responsible for the study: The authors. Funding: The National Cancer Center Research and Development Fund (25‐A‐12) to Dr Saito. Disclosure: All authors have declared no conflicts of interest.